2020
DOI: 10.1002/bjs.11316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of donor nephrectomy time during circulatory-dead donor kidney retrieval on transplant graft failure

Abstract: Background: When the blood supply ceases in a deceased organ donor, ischaemic injury starts. Kidneys are cooled to reduce cellular metabolism and minimize ischaemic injury. This cooling is slow and kidneys are lukewarm during nephrectomy. Smaller single-centre studies have shown that prolonged donor nephrectomy time decreases early kidney transplant function, but the effect on long-term outcome has never been investigated in large multicentre cohort studies. Methods: The relationship between donor nephrectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…58 During this period ('nephrectomy time') organs are subject to additional ischemic damage. None of the DD studies reported on nephrectomy time; differences in which kidney is retrieved last may contribute to inferior outcomes as found by Heylen et al 59 Whilst this is the first meta-analysis comparing right and left DD kidneys, there are three other meta-analyses to our knowledge which attempt to compare right versus left LD kidneys. [21][22][23] All three focus primarily on donor outcomes rather than the recipient outcomes described in this study.…”
Section: Discussionmentioning
confidence: 86%
“…58 During this period ('nephrectomy time') organs are subject to additional ischemic damage. None of the DD studies reported on nephrectomy time; differences in which kidney is retrieved last may contribute to inferior outcomes as found by Heylen et al 59 Whilst this is the first meta-analysis comparing right and left DD kidneys, there are three other meta-analyses to our knowledge which attempt to compare right versus left LD kidneys. [21][22][23] All three focus primarily on donor outcomes rather than the recipient outcomes described in this study.…”
Section: Discussionmentioning
confidence: 86%
“…In our recent Eurotransplant registry study, donor nephrectomy time independently predicted death‐censored graft failure in DCD but not DBD kidneys. For each 10‐min increase in donor nephrectomy time, the odds of graft failure increased by 5% 9 . The magnitude of this effect was comparable to the effect of each additional hour of cold ischemia.…”
Section: Kidneymentioning
confidence: 89%
“…Graft susceptibility to ischemia during donor nephrectomy and implantation depends on donor type with more pronounced detrimental effects in DCD compared to DBD kidneys. In the Eurotransplant registry, increasing donor nephrectomy time increased the risk of graft failure only in DCD and not DBD 9 . The same registry showed a more pronounced effect of implantation time on graft failure in DCD versus DBD 17 .…”
Section: Kidneymentioning
confidence: 94%
See 1 more Smart Citation
“…We thank van Straalen and Minnee for their thoughts regarding surgical time intervals impacting on post‐transplant kidney outcomes.…”
mentioning
confidence: 99%